WORLD BANK GROUP SHARES RESEARCH FINDINGS WITH USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NIBONG TEBAL, July 2015 World Bank Group Malaysia Senior Economist Dr. Frederico Gil Sender was at the Universiti Sains Malaysia (USM) Engineering Campus recently to share their research findings titled ‘Malaysia Economic Monitor: Transforming Urban Transport’.